Chemical and Microbiological Aspects of Meatballs in Tabanan City, Bali - I Made Griya Adi Parta; Ni Made Ayu Suardani Singapurwa; I Putu Candra (Warmadewa University Press, 2019)
This study aims to determine the safety of meatball circulating in Tabanan city in terms of chemical aspects and microbiological aspects referring to the Indonesian National Standard 3818: 2014 concerning bakso (meatball). This research was conducted at the Agriculture Laboratory of the Faculty of Agriculture, Universitas Warmadewa and Denpasar Veterinary Center. This research is an exploratory study that uses experimental design in a laboratory with descriptive analytics. The aspects analyzed were chemical aspects including borax, formalin and microbiological aspects including Escherichia coli and Total Plate Count (TPC). Based on the results of a survey of the number of bakso traders in Tabanan City, 27 traders from 27 traders were taken as many as 14 samples. The test results showed no positive results on borax and formalin testing while the identification of Escherichia coli contamination obtained an MPN value of